2020
DOI: 10.1088/1755-1315/478/1/012024
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fresh and Hay Alfalfa (Medicago sativa L.) Supplementation on Carcass Quality of Hybrid Duck

Abstract: This study aimed to determine the effect of alfalfa fresh or hay supplementation in the diets on the meat quality of hybrid duck. 75 hybrid ducks with 3 treatments and 5 replications were used in this study. Each replication consisted of 5 ducks. The diets were used in the trial consisted of P0 = Basal diets without alfalfa supplementation, P1 = Basal diets + 6% fresh alfalfa supplementation and P2 = Basal diets + 6% alfalfa hay supplementation. Either fresh or hay alfalfa was computed based on dry matter. Dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Additionally, alfalfa contains large quantities of dietary fiber, which could help to lower cholesterol levels. The use of tropical alfalfa (Kacang Ratu BW) in ducks (35 days) from 3% up to a level of 10 % did not affect the production performance of ducks, but reduced FCR ( Suwignyo et al, 2020a , Suwignyo et al, 2020b , Suwignyo et al, 2020c , Suwignyo et al, 2020d , Suwignyo et al, 2021c , Suwignyo et al, 2021d ) reduced cholesterol from 66.5 to 34.8 mg/100 g ( Samur et al, 2020 ) from 177.7 to 116.2 mg/100g (in the liver), 162.9 to 134 mg/100 (in the blood) and reduced LDL from 83.70 to 68.0 mg/dL but increased HDL from 54.6 to 71.96 mg/dL ( Suwignyo et al, 2022 ). The use of 2 % tropical alfalfa in laying hens (hyline 50 weeks old) produced eggs with higher levels of Fe, Zn, beta carotene, vitamin A and antioxidants than controls, respectively 5.6 vs 4.9 mg/100 g, 3.4 vs 1 mg/100 g, 1818.1 vs 1512.7 µg/100 g, 4934.9 vs 4382.9 µg/100 g, 4.9 vs 15.8 %, making it good for nutritional intervention for stunting eradication programs, that are still high in several developing countries, including Indonesia ( Suwignyo and Indartono, 2022 ).…”
Section: Alfalfa As Food and Foragementioning
confidence: 98%
See 3 more Smart Citations
“…Additionally, alfalfa contains large quantities of dietary fiber, which could help to lower cholesterol levels. The use of tropical alfalfa (Kacang Ratu BW) in ducks (35 days) from 3% up to a level of 10 % did not affect the production performance of ducks, but reduced FCR ( Suwignyo et al, 2020a , Suwignyo et al, 2020b , Suwignyo et al, 2020c , Suwignyo et al, 2020d , Suwignyo et al, 2021c , Suwignyo et al, 2021d ) reduced cholesterol from 66.5 to 34.8 mg/100 g ( Samur et al, 2020 ) from 177.7 to 116.2 mg/100g (in the liver), 162.9 to 134 mg/100 (in the blood) and reduced LDL from 83.70 to 68.0 mg/dL but increased HDL from 54.6 to 71.96 mg/dL ( Suwignyo et al, 2022 ). The use of 2 % tropical alfalfa in laying hens (hyline 50 weeks old) produced eggs with higher levels of Fe, Zn, beta carotene, vitamin A and antioxidants than controls, respectively 5.6 vs 4.9 mg/100 g, 3.4 vs 1 mg/100 g, 1818.1 vs 1512.7 µg/100 g, 4934.9 vs 4382.9 µg/100 g, 4.9 vs 15.8 %, making it good for nutritional intervention for stunting eradication programs, that are still high in several developing countries, including Indonesia ( Suwignyo and Indartono, 2022 ).…”
Section: Alfalfa As Food and Foragementioning
confidence: 98%
“…Research on alfalfa has been conducted for agriculture, animal husbandry, healthcare, and food industries. In the fields of agriculture and animal husbandry, research has been conducted using various developmental models at the laboratory scale ( Suwignyo et al, 2017 , Suwignyo et al, 2020a , Suwignyo et al, 2020b , Suwignyo et al, 2020c , Suwignyo et al, 2020d , Suwignyo et al, 2021a , Suwignyo et al, 2021b , Suwignyo et al, 2021c , Suwignyo et al, 2022 , Suwignyo and Sasongko, 2019 ). In animal husbandry, alfalfa is used as highly nutritious forage for both ruminant and non-ruminant animals to increase livestock production and improve the nutrient content of the meat, eggs, and milk produced.…”
Section: Academic Development Of Alfalfamentioning
confidence: 99%
See 2 more Smart Citations
“…The study of Ouyang et al [ 4 ] through feed manipulation with supplementation alfalfa flavonoids at 5, 10, 15 mg/kg showed decreased the total cholesterol and low-density lipoprotein (LDL) levels and increased high-density lipoprotein (HDL). Another study, supplementation 3% fresh alfalfa in the diet showed an increase feed consumption and body weight gain, but supplemented at 6% did not increase live weight, carcass weight, and carcass percentage of hybrid duck [ 5 , 6 ]. The application of forage as a feed supplement in duck not only will benefit gastrointestinal development, but also will economize traditional ingredients which are becoming costly or less available.…”
Section: Introductionmentioning
confidence: 99%